Development of a Dental and Oral Health Education Model with an Authoritative Parenting Approach to Prevent Dental Caries in Early Childhood - Rini, Willia Novita Eka; Rusdi, M.; Siburian, Jodion; Kalsum, Ummi (Jurnal Pendidikan Progresif, 2024)
Abstract: Development of a Dental and Oral Health Education Model with an Authoritative Parenting Approach to Prevent Dental Caries in Early Childhood. Objective: This research aims to develop a dental and oral health education model utilizing an authoritative parenting approach to prevent dental caries in early childhood. Methods: This research used Mixed Methods with a research and development (R&D) design adopting the ADDIE model (analysis, design, development, implementation and evaluation). Validation tests were carried out by 2 experts (an expert in the field of dental public health and an expert in the field of early childhood education) and 1 practitioner. Next, one-on-one trials were carried out on 3 mothers who had children aged 3-5 years, small group trials on 9 mothers and their children, field trials on 20 mothers and their children for the intervention group, 20 mothers and their children for the control group. Qualitative data analysis used the Miles-Hubermen analysis technique, quantitative data analysis used the Wilcoxon and Mann Whitney tests. Findings: The design stage yielded a dental and oral health education model employing an authoritative parenting approach to prevent dental caries in early childhood. Results from the development stage, including validation by experts and practitioners, affirm the model's suitability for trial. One-on-one and small group tests indicate that the educational model is engaging and easy to comprehend. The field test results demonstrate a significant impact of the provided educational model on enhancing mother's knowledge, attitudes, and improving OHIS value of their children. Conclusion: The dental and oral health education model, employing an authoritative parenting approach to prevent dental caries in early childhood, is deemed suitable for implementation and proves effective in enhancing mother’s knowledge, attitudes, and OHIS value of their children. Keywords: dental caries, early childhood, educational model.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202417